APPLICATION OF INHIBITOR ANALYSIS FOR STUDYING MECHANISMS AND ACTIONS OF POLYMURAMYL, A MURAMYL PEPTIDE-BASED IMMUNE MODULATOR - M. V. Pashenkov (SPb RAACI, 2014)
In present study, the following low-MW inhibitors were used to dissect mechanisms of action for two muramyl peptide components of Polymuramyl, an immunomodulatory drug: (1) N-acetyl-D-glucosaminyl-(β1→4)-N-acetyl-D-muramoyl-L-alanyl-D-isoglutaminyl-meso-diaminopimelic acid (GMtri); (2) a dimeric   muramyl peptide (diGMtetra), wherein two monomers [N-acetyl-D-glucosaminyl-(β1→4)-N-acetyl-D-muramoyl-L-alanyl-D-isoglutaminyl-meso-diaminopimeloyl-D-alanin] are linked via an amide bond between the carboxyl group of terminal D-alanin at one monomer and the ω-amino group of meso-diaminopimelic acid at another monomer. In vitro production of tumor necrosis factor (TNF) by human macrophages stimulated with GMtri or diGMtetra was shown to be inhibited by SB203580 (a RIP2 kinase inhibitor), genistein (a protein tyrosine kinase inhibitor) and BAY 11-7082 (an IκB-kinase inhibitor). Moreover, response to diGMtetra was inhibited by dynasore (an inhibitor of clathrin-dependent endocytosis), as well as by a broad-range protease-inhibiting cocktail. Thus, activating effects upon macrophages induced by the Polymuramyl components is provided by, at least, three biological processes: (1) clathrin-dependent endocytosis; (2) peptidase-mediated processing of diGMtetra; 3) activation of a signal chain RIP2 – IκB-kinase – NF-κB transcription factor.